2013
DOI: 10.15376/biores.8.2.2805-2826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fungal Deterioration in Liquidambar orientalis Mill. Heartwood by FT-IR and Light Microscopy

Abstract: The chemical and morphological changes in heartwood specimens of Liquidambar orientalis Mill. caused by the white-rot fungus Trametes versicolor and the brown-rot fungi Tyromyces palustris and Gloeophyllum trabeum were studied by wet chemistry, FT-IR, GC-MS analyses, and photo-microscopy. According to GC-MS results, 26 extracts identified in the ethanol/toluene extraction and 17 in the ethanol extraction were found. Heartwood specimens of L. orientalis were highly susceptible to the fungi tested. While 1% NaOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…The C–H found in cellulose, cellulose, hemicelluloses and the CO and cellulose present in lignin express the C–O bonds in hemicelluloses. The relationship of these peaks with polysaccharides has been reported in the literatüre . These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The C–H found in cellulose, cellulose, hemicelluloses and the CO and cellulose present in lignin express the C–O bonds in hemicelluloses. The relationship of these peaks with polysaccharides has been reported in the literatüre . These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature.…”
Section: Resultssupporting
confidence: 90%
“…The relationship of these peaks with polysaccharides has been reported in the literatüre. 33,45,57,[61][62][63] These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature. Yildiz et al 64 in their study found that in parallel with the increase in the UV exposure time, these peaks decreased in coniferous wood species, while they increased in leafy wood species.…”
Section: Surface Composition Of Wood After Natural Weatheringsupporting
confidence: 92%
See 2 more Smart Citations
“…For instance, lianas have RP cells that are thin-walled, which is speculated to allow for increased twisting without rupture (Schenck, 1893; Haberlandt, 1914; Sieber and Kučera, 1980; Gartner, 1991; Putz and Holbrook, 1991). In Liquidambar , however, the rays have an even higher specific gravity (relative density) than the surrounding fibers (Taylor, 1969), which may explain why their cell walls are resistant against a number of important fungi to a high degree, while the fibers are easily digested (Yilgor et al, 2013). The high anatomical variation in the structure of rays (Chattaway, 1951), from their height through to their width and connectivity with AP, could also help evaluate the effectiveness of wall 3 between species.…”
Section: Rap and The Codit Model – A Frameworkmentioning
confidence: 99%